Differential responses of genes and enzymes associated with ROS protective responses in the sugarcane smut fungus. Issue 12 (December 2020) - Peters, L.P.; Teixeira-Silva, N.S.; Bini, A.P.; Silva, M.M.L.; Moraes, N.; Crestana, G.S.; Creste, S.; Azevedo, R.A.; Carvalho, G.; Monteiro-Vitorello, C.B.
Abstract: The fungal pathogen Sporisorium scitamineum causes sugarcane smut disease. We have previously shown that resistant sugarcane plants induce ROS, coinciding with a delay in fungal colonization. Here, we investigated whether the fungus modifies the enzymatic antioxidant system in vitro and when colonizing sugarcane tissues in response to ROS. In vitro, the exposure to ROS did not affect cell integrity, and a combination of superoxide dismutases (SOD) and catalases (CAT) were active. In vitro, the fungus did not alter the expression of the transcriptional regulator Yap1 and the effector Pep1. The fungus activated distinct enzymes when colonizing plant tissues. Instead of CAT, S. scitamineum induced glutathione peroxidase (Gpx) expression only when colonizing smut-resistant plants. Yap1 had an earlier expression in both smut-susceptible and -resistant plants, with no apparent correlation with the expression of antioxidant genes sod, cat, gpx, or external redox imbalance. The expression of the effector pep1 was induced only in smut-resistant plants, potentially in response to ROS. These results collectively suggest that S. scitamineum copes with oxidative stress by inducing different mechanisms depending on the conditions (in vitro/in planta) and intensity of ROS. Moreover, the effector Pep1 is responsive to the stress imposed only by the sugarcane resistant genotype. Highlights: The smut pathogen exhibited differential responses to ROS in vitro and in planta . In vitro, the fungus activated SOD and CAT in the presence of ROS. In planta, the fungus induced GPX gene expression only in smut resistant plants. The transcription factor Yap1 had an earlier expression in planta . The smut-pathogen induced the effector Pep1only in resistant plants.